The Growth of Digital Financial Services (DFS) in Indonesia Amid Tight Regulations: Drivers and Barriers Analysis - Asep Koswara (PT. Faaslib Serambi Media, 2024)
This study explores the dynamics of digital financial services (DFS) growth in Indonesia amidst increasing regulatory challenges. Using a qualitative observational approach, the research investigates the key drivers and barriers to DFS expansion in the country. The findings reveal that the gross transaction value (GTV) of online payments in Indonesia reached 286 billion in 2022, with projections to grow by 19% annually to 404 billion by 2024. Similarly, the online lending sector saw an increase in loan balances, from 5 billion in 2022 to an expected 9 billion by 2024. The research identifies key drivers such as technological advancements, the increasing smartphone penetration, and a more supportive regulatory environment as factors contributing to the sector’s growth. However, challenges /barrier remain, particularly in terms of regulatory constraints, digital literacy gaps, and infrastructure limitations in rural areas. This paper also explores the potential implications of stricter regulations on fintech innovation and its effects on market competition. It concludes by offering recommendations for enhancing digital financial inclusion, including the need for targeted policy reforms, investment in digital literacy, and improved internet infrastructure.